Design and Development of a Web-Based Information System for Palm Oil Derivative Product Education - Febriani Putri Wulandari; Ritna Wahyuni; Andi Prayogi; M. Ilham Saputra (Academic Bright Collaboration, 2026)
Purpose – Public literacy regarding palm oil derivative products remains limited, while structured and accessible educational resources are still scarce. This study aimed to design and develop a web-based information system that provides organized educational content on palm oil derivative products and supports public access to information on downstream palm oil industries. Methods – This study employed a library research approach using secondary data from scientific literature, government publications, and official references related to palm oil derivative products. System requirements were analyzed and modeled using Unified Modeling Language (UML). The system was developed using HTML, CSS, PHP, MySQL, the Laravel Framework, and Laragon. Functional evaluation was conducted using Black Box Testing on 14 core system features. Findings – The study produced a web-based educational information system containing categorized content on oleofood, oleochemical, and bioenergy products, supported by article, video, search, and administrative content-management features. Functional testing showed that all 14 test scenarios were successfully completed, resulting in a functional success rate of 100%. Research implications – The findings indicate that the system is functionally reliable for delivering structured educational information on palm oil derivative products. However, the evaluation was limited to functional testing and did not assess usability, user satisfaction, or educational effectiveness. Originality – This study contributes a specialized web-based educational platform that integrates categorized palm oil derivative product information, multimedia resources, and centralized content management within a single system.